Methodology for Current Account and Exchange Rate Assessments - Kincaid, G. (Occasional Papers; Occasional Paper ;, 2001)
This chapter reports on Coordinating Group on Exchange Rate Issues' (CGER) works and provides perspectives on alternative frameworks for assessing exchange rates and the rationale for CGER's general approach. The primary motivation for the work of the CGER is to identify cases where exchange rates appear to be substantially out of line with medium-run macroeconomic fundamentals. It is recognized that such situations can have different interpretations, depending on the cyclical positions of economies and other circumstances. The assessments of exchange rates among industrial country currencies rely primarily on an application of a macroeconomic balance framework. This framework focuses on the extent to which the current account positions associated with prevailing exchange rates are consistent with medium-run fundamentals. Substantial discrepancies between exchange rates and their medium-run equilibrium levels, when they emerge, raise two different, however, related issues for the IMF to address in its exercise of bilateral and multilateral Surveillance.